3x-2=6(x-5)

Simple and best practice solution for 3x-2=6(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2=6(x-5) equation:



3x-2=6(x-5)
We move all terms to the left:
3x-2-(6(x-5))=0
We calculate terms in parentheses: -(6(x-5)), so:
6(x-5)
We multiply parentheses
6x-30
Back to the equation:
-(6x-30)
We get rid of parentheses
3x-6x+30-2=0
We add all the numbers together, and all the variables
-3x+28=0
We move all terms containing x to the left, all other terms to the right
-3x=-28
x=-28/-3
x=9+1/3

See similar equations:

| -126=7v | | 54x=562 | | 11n=1.21 | | 3(3-2x)=3(3x+1) | | 5x-1=3x-41 | | 1/22x+2=13 | | 1/2x+1=10.5 | | x=1.8-0.8+9x^2-10x^2 | | 3x-2/2=13 | | 7x²-10x-8=0 | | 1/4x+2=6.75 | | (10x+24)^0.5=(x+12) | | g/2+1=6 | | 5(x-75)=50 | | 0.35/(2/3x)=0.45/(x−10) | | 10+8z=+3–10 | | n^2+7n-264=0 | | 90=1/2(14+16)h | | 7x+6=195 | | 4(3m+6)-3(2m+9=9) | | 12-(6+x)=(12-6)+x | | x2/6=12 | | 1/10x+2=4 | | 3.7y=20.72 | | -4+3x=-6x+10 | | x/3–7=10 | | 40=4/3x | | 2(2x+1)=3x-9x | | 4x-4÷4=-2 | | 4.8=e-3.2 | | 4+35=20x+13 | | 1/4x-2=2.25 |

Equations solver categories